Improvement in coronary microvascular dysfunction evaluated by cardiac magnetic resonance in patients with hypertrophic obstructive cardiomyopathy after transapical beating-heart septal myectomy - Zhao, Yun; Huang, Lu; Li, Chenhe; Tang, Dazhong; Luo, Yi; Xiang, Chunlin; Zhou, Xiaoyue; Fang, Jing; Wei, Xiang; Xia, Liming (Frontiers in Cardiovascular Medicine, 2023)
Background Coronary microvascular dysfunction (CMD) is a pathophysiological mechanism underlying hypertrophic obstructive cardiomyopathy (HOCM). However, few studies have investigated the potential effect of transapical beating-heart septal myectomy (TA-BSM) on coronary microvascular function. This study aimed to evaluate coronary microvascular function in HOCM after TA-BSM using cardiac magnetic resonance (CMR) and to investigate the determinants of improvement in coronary microvascular dysfunction. Materials and methods 28 patients with HOCM who underwent TA-BSM were prospectively enrolled in this study from March 2022 to April 2023. All patients received CMR before and after TA-BSM. CMR-derived parameters were compared, including the maximum wall thickness, native T1 value, T2 value, late gadolinium enhancement (LGE), and perfusion indexes (Slopemax, Timemax, and Slmax). Univariate and multivariate linear regression identified variables associated with the rate of Slopemax change. Results Compared with the preoperative parameters, left ventricular function and myocardial perfusion were significantly improved after TA-BSM (all P < 0.05), although still lower than in healthy controls. In the analysis of the myocardial perfusion parameter rate of change, the rate of Slopemax change was the most significant (P = 0.002) in HOCM. In the multivariable regression analysis, age (adjusted β = 0.551), weight of the resected myocardium (adjusted β = 0.191), maximum wall thickness (adjusted β = −0.406), LGE (adjusted β = 0.260), and Δ left ventricular outflow tract (LVOT) pressure gradient (adjusted β = −0.123) were significantly associated with the rate of Slopemax change in HOCM (P < 0.05 for all). Conclusion Coronary microvascular dysfunction in both hypertrophic and non-hypertrophic myocardial segments was improved in patients after TA-BSM. Microcirculatory perfusion evaluated by CMR can be a potential tool to evaluate the improvement of CMD in HOCM.